Gene Association with Leprosy: A Review of Published Data - Mazini, Priscila Saamara; Alves, Hugo Vicentin; Reis, Pâmela Guimarães; Lopes, Ana Paula; Sell, Ana Maria; Santos-Rosa, Manuel; Visentainer, Jeane Eliete Laguila; Rodrigues-Santos, Paulo (Frontiers in Immunology, 2016)
Leprosy is a chronic infectious disease caused by an obligate intracellular bacterium known as Mycobacterium leprae. Exposure to the bacillus is necessary, but this alone does not mean an individual will develop clinical symptoms of the disease. In recent years, several genes have been associated with leprosy and the innate immune response pathways converge on the main hypothesis that genes are involved in the susceptibility for the disease in two distinct steps: for leprosy per se and in the development of the different clinical forms. These genes participate in the sensing, main metabolic pathway of immune response activation and, subsequently, on the evolution of the disease into its clinical forms. The aim of this review is to highlight the role of innate immune response in the context of leprosy, stressing their participation in the signaling and targeting processes in response to bacillus infection and on the evolution to the clinical forms of the disease.